Targeted Radionuclide Therapy for the Treatment of Metastatic Bone Disease: A Retrospective Analysis in Moscow, Russia - Poppy Filmonov; Ayesh Mahmood (Sriwijaya Journal of Radiology and Imaging Research, 2025)
Introduction: Metastatic bone disease (MBD) is a common complication of advanced cancer, causing significant morbidity and negatively impacting patients' quality of life. Targeted radionuclide therapy (TRT) has emerged as a promising treatment modality for MBD, offering targeted delivery of therapeutic radiation to bone metastases while minimizing damage to healthy tissues. Methods: A retrospective cohort study was conducted at leading oncology centers in Moscow, Russia, between 2018 and 2023. Patients with MBD who received TRT with either Strontium-89 or Samarium-153 were included. Data on patient demographics, primary tumor type, number of bone metastases, pre-treatment pain scores, performance status, and survival outcomes were collected. Results: A total of 150 patients were included in the study (mean age 62 years, 55% female). The most common primary tumor types were prostate (35%), breast (25%), and lung (15%). The median number of bone metastases was 5 (range 1-20). Pre-treatment pain scores were high (median 7 on a 0-10 scale). A significant reduction in pain scores was observed post-TRT (median 3, p<0.001). Overall survival at 1 year was 75%, with a median survival of 18 months. Favorable prognostic factors included a lower number of bone metastases, good performance status, and absence of visceral metastases. Conclusion: TRT is a safe and effective treatment option for patients with MBD in Moscow, Russia, offering significant pain palliation and improved quality of life.